EFFECTIVENESS OF DEVELOPMENT OF SMASH BALL VOLLEY SKILLS EXERCISE MODEL FOR BEGINNERS OF AGE OF HIGH SCHOOL - Abdillah Mustaqim; Susilo; Widiastuti (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The aim of this study is to prove the effectiveness of the volleyball smash skill training model for high school age beginners produced. The research method used in this study is the research and development method of Borg and Gall using 10 stages and the subject of the study is beginner high school age athletes in East Jakarta. Effectiveness test, the significance of the difference test with SPSS 16 paired sample test obtained the accuracy of the experimental group with an average value of 10.63 and the control group with an average value of 3.23 This difference value is the average value of increased test results in group skills. Selection of the average results of the different values ​​of the experimental group and the control group or mean difference = 0.127, t-count = 7.765 df = 60, with p-value = 0.000 <0.05. Significant differences between the experimental and control groups. These results indicate that the treatment given to the experimental group that is the volleyball smash skill training model for high school age beginners has a higher effectiveness and can improve the volleyball smash skill for high school age beginners.